Assessment of patient satisfaction with the preoperative anaesthetic evaluation - Lee, SY; Cheah, Saw Kian; Muhammad M,; Aniza Ismail, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Preoperative anaesthetic evaluation is important in the perioperative care. The aim of the study was to evaluate the level of satisfaction and factors affecting patient satisfaction in the preanaesthetic clinic (PAC). A total of 304 patients who attended PAC for preoperative evaluation were recruited into this study. A bilanguage validated Patient Satisfaction Survey in English and Bahasa Malaysia with total questions of 18 examining non-provider factors (NPF) (facilities and appropriateness of waiting time) and provider factors (PF) (doctor, counter services, nurses and supporting staff) were utilized. The survey form was graded in a strongly agree/ disagree five-point Likert scale format for patients’ level of satisfaction. Overall satisfaction of preoperative evaluation was reported as 98.7% with mean scores from doctor (4.49 + 0.60), counter service (4.48 + 0.61), support staff (4.47 + 0.62) and the NPF (4.40 + 0.62), respectively. All factors were found to be significantly correlated with the overall patients’ satisfaction (p<0.001) and waiting time shown to be the independent predictor affecting the level of satisfaction. Overall majority of the patients were satisfied with the preoperative evaluation provided at PAC and both non-provider and provider factors were shown to have a significant impact on patient satisfaction.